Analysis of Factors Influencing Purchase Decisions of Paldo Coffee BTS Edition Products (Case Study of BTS Fans) - Amanda, Fadila (LPPM Universitas Sari Mulia, 2025)
Paldo coffee is a ready-to-drink coffee originating from Korea and consists of two flavor variants, namely americano and coffee latte which are packaged in contemporary bottles, where this drink is suitable for all circles, especially millennials, especially the ARMY fandom. The type of research used is quantitative research by distributing questionnaires via Google Form to consumers who have purchased BTS Paldo coffee products at least once or more. The purpose of this study is to analyze what factors influence BTS fans in buying BTS's Paldo coffee products. The results showed that the brand ambassador and brand image became the dominant factor for BTS fans in buying BTS paldo coffee with a loading factor value of 67.941%.